Microbioma do solo associado ao cajueiro (Anacardium occidentale L.): Composição, diversidade e funções - Campos, Arlene Santisteban (2023)
The cashew tree (Anacardium occidentale L.), originally from Brazil, belongs to the Anacardiaceae family and is widely cultivated in northeastern Brazil, where it occupies a prominent place among tropical fruit trees. However, there is little information about the microorganisms present in the soil associated with the cashew tree. The objective of this work was to evaluate the influence of cashew tree genotypes, soil management, seasonality and edaphic conditions on the health and microbial structure present in the soil at four cashew producing regions. Soil collections were carried out in the municipalities of Beberibe and Pacajus (Ceará), Serra do Mel (Rio Grande do Norte) and Pio IX (Piauí). In each of these areas, soils under cultivation of cashew trees of the common genotypes and the CCP 76 cultivar were collected, in the rainy and dry seasons. For the cultivar CCP 76, the collections were carried out in areas of cultivation under two management intensities. Chemical and physical analyzes of the soil were carried out. For microbial analysis, basal respiration, microbial biomass carbon and metabolic and microbial quotients were determined. Enzymatic analyzes of β-glucosidase (BGL), arylsulfatase (ARS) and acid (FAC) and alkaline (FAL) phosphatases were performed. DNA sequencing was performed using the Illumina MiSEq platform, from PCR amplification of 16S rRNA genes in the V4 region, primers 515F and 806R. Sequencing data were treated and analyzed in RStudio, verifying the rarefaction curve, alpha (Simpson, Shannon and Chao1) and beta diversities, abundance of taxa, community structure through non-metric multidimensional scaling (NMDS) analyses. , followed by a principal coordinate analysis (PCoA) and a discriminant linear effect size analysis (LEfSe), as well as indicator species analysis and functional prediction. It is concluded that the quality and structure of the soil microbial community were affected by the genotype, management, seasonality and edaphic attributes of the analyzed areas. The copyotrophic and oligotrophic nature of Bacillota and Actinomycetota, respectively, was a key factor for the differentiation of soil microbial diversity related to cashew genotypes in the Serra do Mel region. Actinomycetota was more resource efficient than Bacillota. Soils with high levels of Fe and Cu had a greater abundance of taxa (bacteria and Archaea) oxidizing ammonia. Management was a very important factor for the increase in soil microbiota richness in Pacajus. BGL was positively related to total soil organic carbon and ARS to bacteria from the phylum Proteobacteriota and Verrucomicrobiota.